DRYING OF INVALUABLE PRODUCTS OF CUTTING OF FISHES BY MANUFACTURE OF DRY BASES FOR BROTHS, SOUPS AND SAUCES OF FAST PREPARATION - L. V. Antipova (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2012)
On the basis of experimental researches drying curves are constructed, modes of drying of invaluable products of cutting of fishes are proved. Low temperature modes and a short cycle of drying allows to receive dry bases with high extraction Singular extraction Plural extractionsability, applicable for preparation of broths, soups and sauces of fast preparation